The Influence of Community Participation on the Sustainability of Public Health Service Innovation in Makassar City - Haerana, Haerana; Fatmawati, Fatmawati; Burhanuddin, Burhanuddin; Sudarman, Fatmawada (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2024)
Public service innovation can be developed if there is synergy between the government, institutions as innovators, and the community. The purpose of this study was to measure the influence of community participation on the sustainability of public health service innovation programs in Makassar City. This type of quantitative research with data collection methods was carried out by distributing questionnaires and documentation, and data analysis using SPSS 21. The results of the significance test (t-test) showed that there was a probability value of 0.000 ≤ 0.05. This value can prove that community participation has a positive and significant effect on the sustainability of innovation. Simultaneous testing (F) obtained an F count of 908,705 and a probability of 0.000. Because sig 0.000 <0.05, it can be concluded that the community participation variable affects the sustainability of innovation. While the magnitude of the coefficient of determination (adjusted R2) = 0.695, meaning that the community participation variable affects the innovation sustainability variable by 69.5%, the remaining 30.5% is influenced by other variables not included in this research model.